The Urban migrant future desire : a study of reverse migration in Malaysia / Nur Huzeima Mohd Hussain, Hugh Byrd and Nur Azfahani Ahmad - Nur Huzeima, Mohd Hussain; Byrd, Hugh; Nur Azfahani, Ahmad (Universiti Teknologi MARA, Perak, 2017)
Globalisation combined with resources of oil and gas hasled to an industrial society in Malaysia. For the past 30 years, rapid urban growth has shifted from 73% rural to 73% urban population. However, the peak oil crisis and economic issues are threatening the growth of urbanisation and influencing the trends of population mobility. This paper documentsthe beginnings of a reverse migration (urban-to-rural) in Malaysia. The method adopted case study that involves questionnaires with the urban migrants to establish the desires, definite intentions and reasons for future migration. Based on this data, it predicts a trend and rate of reverse migration in Malaysia.